Visible light-assisted degradation of 4-nitrophenol and methylene blue using low energy carbon ion-implanted ZnO nanorod arrays: Effect on mechanistic insights and stability. (January 2022) - Kumar, Dharman Ranjith; Ranjith, Kugalur Shanmugam; Haldorai, Yuvaraj; Kandasami, Asokan; Rajendra Kumar, Ramasamy Thangavelu
Abstract: The present investigation demonstrates an enhancement of the visible photocatalytic activities by C ion implantation in ZnO nanorod arrays (NRAs). Vertically aligned ZnO NRAs were prepared by seed layer assisted solution-phase growth and implanted with 70 keV carbon ions at various fluencies: 1E15, 5E15, 1E16, and 3E16 ions/cm 2 . X-ray diffraction and FESEM results revealed the crystalline 1D ZnO NRAs having a length of ∼3 μm with a diameter in the range of 150–200 nm. C implantation induces the absorption towards the visible region and a substantial decrease in the optical bandgap energy from 3.2 eV to 2.43 eV. The photocatalytic activities (PC) of C ion-implanted ZnO NRAs were investigated through the degradation of 4-Nitrophenol (4-NP) and methylene blue dye (MB) under ambient visible light irradiation. The degradation efficiency of C ion-implanted ZnO NRAs increases compared to the pristine ZnO NRAs from 60.12% to 93.7% and 48.6 to 97.5% for MB and 4-NP, respectively. The synergistic effects of low energy carbon ion-induced bulk and surface interface electronic states facilitate a narrow band of visible light absorption and efficient charge separation to increase the visible-light-driven photocatalytic performance of ZnO NRAs. Highlights: Preparation of vertically aligned C-ion-implanted ZnO NR arrays for pollutant degradation. The C-ion- implanted ZnO arrays photodegradated 97.5% of 4-nitrophenol. The C-ion- implanted ZnO arrays degraded 93.7% of MB dye under natural light. Photocatalytic activity increases with the fluence of C-ion on ZnO NR arrays.